(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores the important role of parents in the education and upbringing of children diagnosed with Autism Spectrum Disorder (ASD). This emphasizes the importance of parental involvement in ensuring effective education and social integration for children. Research highlights the need for parents to work closely with teachers and therapists to create individualized education plans. In addition, the article discusses strategies for fostering communication, managing behavior problems, and creating a supportive home environment to help children develop. Research suggests that conscious and active parental involvement significantly increases a child’s ability to cope with ASD.